Research on the legal aspects of chatbots; Analysis of Personality Rights, Civil responsibility, and Intellectual Property - Zahra Shakeri; Mohammad Matin Miladi qomi (حقوق فناوریهای نوین)
Chatbots are a modern manifestation of artificial intelligence that are now placed for public interaction and conversation with individuals. They can engage in a two-way interaction with a user, responding to their questions and even offering suggestions. This system is based on the capabilities arising from the development of artificial intelligence and is continuously advancing. Among these, the legal issue concerns whether chatbots are responsible for what they respondand whether what they provide is their intellectual property. Essentially, can personalities be attributed to chatbots? The present article finally concludes, with the analytical-descriptive approach, that chatbots may potentially possess a degree of personality in the future, but in current circumstances, the effects and content provided by chatbots are attributed to their owners and creators. Although their development and the reinforcement of chatbots' autonomy can pose numerous challenges to classical legal theories.